Long-term functional outcomes of patients with Hirschsprung disease following pull-through - Gunadi, Gunadi; Carissa, Theodora Monica; Stevie, Stevie; Daulay, Ezzah Fatmala; Yulianda, Dicky; Iskandar, Kristy; Dwihantoro, Andi (BioMed Central Ltd, 2022)
Background: Hirschsprung disease (HSCR) is a common congenital disorder presenting with functional obstruction due to aganglionosis of the colon. There are numerous types of pull-through surgery for managing HSCR, such as transabdominal endorectal (Soave), Swenson, Duhamel, transanal endorectal pull-through (TEPT), and laparoscopic (Georgeson) approach. Here, we aimed to describe the long-term outcome of patients with HSCR who underwent transabdominal Soave, Duhamel, and TEPT in our institution. Methods: We performed a cross-sectional analysis for patients who underwent Duhamel, Soave, and TEPT at our institution from January 2012 to December 2015. Long-term functional outcome was determined by bowel function score (BFS). The BFS was obtained by interviewing patients who had completed at least three years of follow-up. Results: Twenty-five patients were included in this study who underwent transabdominal Soave (n = 8), Duhamel (n = 4), and TEPT (n = 13). There were 24 patients with short aganglionosis type. The median age of HSCR diagnosis was 10 (IQR = 1–39) months, while the median age of pull-through surgery was 17 (IQR = 7–47) months. The median follow-up of BFS level for HSCR patients after pull-through was 72 (IQR, 54–99) months. There were 11 patients with good BFS level and 10 patients with normal BFS level. Additionally, 50 of Duhamel patients had poor BFS level, while 50 of Soave patients had good BFS level, and 54 of TEPT patients had normal BFS level (p = 0.027). As many as 50 of Duhamel patients showed daily soiling and required protective aids, while 38.5 of TEPT had staining less than 1/week and no change of underwear required, and 50 of Soave patients revealed no soiling, respectively (p = 0.030). Furthermore, 75 of Duhamel patients had accidents, while 75 of Soave and 46.2 of TEPT patients had no accidents (p = 0.035). Conclusion: Our study shows that the type of definitive surgery might affect the long-term bowel functional outcome; particularly, the TEPT approach might have some advantages over the transabdominal Soave and Duhamel procedures. © 2022, The Author(s).